CHEMICAL COMPOSITION OF LAVENDER (Scientific journal of the Fergana State University, 2023)
This article describes the experimental determination of the macro - and trace element composition of the lavender plant using the AVIO 200 optical emission spectrometer and the places of application of this medicinal plant in traditional medicine. It is specifically for such growing neurological diseases among the population, such as irritability, fatigue of the nervous system, deterioration of memory, can be obtained a good effect from the use of the medicinal plant lavender.